A Rare Case of Hypercalcemia from Mediastinal Ectopic Hyperparathyroidism - Nasrin Dhapa; Lamar Alocozy; Rumana Khan (Journal of Cardiovascular Development and Disease, 2025)
Hypercalcemia is frequently attributed to primary hyperparathyroidism, commonly a result of parathyroid adenomas. Ectopic hyperparathyroidism is characterized by hyperfunctioning parathyroid tissue located outside of expected anatomical locations of endocrine tissue. In this report, we present a rare case of hypercalcemia secondary to a mediastinal ectopic parathyroid adenoma, located between the left atrium and pulmonary artery. Given the unique location of the ectopic gland, diagnosis was delayed with additional complications that followed due to difficulty accessing the gland surgically. Despite this, urgent surgical removal of the ectopic gland allowed for remarkable improvement in presenting symptoms. This clinical case highlights diagnostic and therapeutic challenges that present a unique situation worthy of clinical discussion.